(untitled) (Eurasian Journal of Ecology, 2025)
Uranium mining activities in Northern Kazakhstan - contributed to an increase in the active concentration of natural radionuclides in the environment. The purpose of this study is to assess the characteristics of the spatial distribution of natural radionuclides in surface water bodies and lake sediments of a typical uranium mining area located near the reclaimed deposits of Tastykol (Mine №9) and Zaozornoye (Mine №8) located in the Akmola region, also to understand the processes of their migration is the study of the geochemical features of natural radionuclides in water and sediments. The Alpha and activity of natural radionuclides in water bodies and bottom sediments was determined, as well as the alkalinity level (PH) was immediately determined during sampling when taking water samples. Measurements of the power of the gamma radiation dose were carried out in waste rock dumps in the territories of Mines and in the territories of quarries, sampled water bodies. Our research work showed the following: alpha activity in samples of water bodies in the study area covered the range from 0.8 to 9.8 Bk/l, beta activity - from 0.3 to 2.7 Bk/l. This ratio of values indicates an increased potential health risk due to radiation exposure in these specific areas. The alpha activity value in the bottom sediment is in the range of 250 Bk/kg – 510 Bk/kg, beta activity is in the range of 120 Bk/kg – 240 Bk/kg. High values are at a high level in the territories of Koksor, Tastykol, quarry №5 of Mine №9, where there were mainly man-made impacts. An increase in the measured level of alkalinity – indicates an increased potential man-made impact. Keywords: ore management, reclamation, aeroradiometry, air conditioners, ore phenomena, uranium mining, ionizing radiation sources